Proses Migrasi dan Peran Teknologi Komunikasi di antara Pekerja Migran di Batam - Indonesia: The Process of Migration and Communication Technology Roles among Labor Migrants in Batam - Indonesia - Inayah Hidayati (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
This research explains the roles of communication technology on the migration process of labor migrants in Batam, Indonesia. Differences between places are strong reasons for people to migrate. The advances in communication technology have freed up opportunities for people to migrate. Technology has made it more accessible for migrants to raise links to their next destination through the internet. Interactions within communication technology make migration easier by decreasing the expenses and risks of moving. The explanations in this study are to understand the communication technology for the migrating process and calculate the social networks of migrants. This research applied mixed methods to explore the migration process with data collected included quantitative data from a survey with 500 respondents and supported by qualitative data from in-depth interviews. The results: 1) Communication technology helps migrants in the migration process, especially for searching for information about the destination area. 2) The migrant who uses communication technology has a strong social network and less risk of migration. The role of communication technology in the migration's processes is as a tool to maintain social ties of migrants, migrant uses their social media to make contact and gain information about their destination. This study related to SDGs' target number 10.7 which facilitates orderly, safe, regular and responsible migration and mobility of people, including through the implementation of planned and well-managed migration policies, communications technology facilitate safe and well-managed migration.